Effects of elemene on inhibiting proliferation of vascular smooth muscle cells and promoting reendothelialization at the stent implantation site. (15th May 2017) - Sun, Wenjie; Huang, Yuhua; Yin, Tieying; Wang, Jingjing; Du, Ruolin; Qiu, Juhui; Zhang, Yuan; Wang, Yazhou; Chen, Jinju; Wang, Guixue
Abstract : Elemene coated stents prepared by electrospray could inhibit proliferation of VSMCs and promote endothelialization after implantation into rabbit iliac arteries. Abstract : Anticancer drugs are commonly used as inhibitors of vascular smooth muscle cell (VSMC) proliferation in clinical treatments. This study aims to investigate how elemene affects the proliferation of VSMCs, the restenosis, and the reendothelialization after implanting the elemene-coated stents. VSMCs derived from rat aorta were used to test the cell proliferation, cell cycle, migration, apoptosis, cytoskeletal protein F-actin, intracellular Ca 2+, IncRNA chip and gene expression of PCNA, P53, and Cx43 when cultured with elemene. It was found that elemene can inhibit proliferation, induce apoptosis and block the connections between VSMCs in a dose-dependent manner. IncRNA chip analysis has revealed that there was a significant difference in the expression of 1417 genes and 34 signaling pathways. Elemene liposome membranes prepared by electrostatic spray could also inhibit the proliferation of VSMCs. In addition, after implanting the elemene-coated stent into a rabbit iliac artery for 12 weeks, the surface of elemene-coated stents was fully covered with a layer of neointima and a few platelets. However, a large number of platelets aggregated and attached on the uncoated stents (control samples). In conclusion, elemene could inhibit VSMC proliferation in vitro, which involved the regulation of various signal transduction pathways, and elemene-coated stents could promote endothelialization after stent implantation. Thus, elemene has great potential for the clinical treatment of restenosis and reendothelialization.